Normal forms of kinematic singularities of 3R robot manipulators - Tchoń, Krzysztof (Zielona Góra: Uniwersytet Zielonogórski)
Using the singularity theory approach we study kinematic singularities of 3R robot manipulators satisfying certain geometric conditions. A classification of singular configurations is set forth and three mathematical models (normal forms) of the kinematics around singular configurations are derived.
Keywords: sterowanie; sterowanie-teoria; sztuczna inteligencja; matematyka stosowana; informatyka